Pengenalan Budidaya Jamur Tiram sebagai Media Pembelajaran pada Anak Usia Dini di Instalasi Kebun Percobaan Faperta Universitas Palangka Raya: Introduction to Oyster Mushroom Cultivation as a Learning Medium for Early Childhood at the Experimental Garden Installation, Faculty of Agriculture, University of Palangka Raya - Atikah, Titin Apung; Rachman, M. Aulia; Saptono, Mofit; Syahid, Abdul; Elvince, Rosana; Widyawati, Wahyu; Sirenden, Ruben Tinting; Rahayu, Yekti Sri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The cultivation of oyster mushrooms is an activity that can be introduced to early childhood as an effective learning medium. This activity not only familiarizes children with the growth process of oyster mushrooms but also increases their awareness of the importance of the environment and sustainability. At the Experimental Garden Installation of the Faculty of Agriculture, University of Palangka Raya, this program is designed to provide a fun and educational learning experience for the Early Childhood Education (PAUD) Tiara Az Zahra. Through the introduction of oyster mushroom cultivation, it is expected that children can develop observation skills, knowledge about the life cycle of mushrooms, and awareness of the importance of mushrooms as a nutritious vegetable source in everyday life. Additionally, this activity also aims to bring children closer to the world of science from an early age, as well as teach values of cooperation and responsibility through practical and interactive activities.